The book of nursery rhymes : 50 classic poems for children - Gliori, Debi (DK Publishing, 2024)
Here are 50 classic nursery rhymes, beautifully illustrated by Debi Gliori. Have fun reading along with your little one as you introduce them to well-known nursery rhymes including, Humpty Dumpty, Incy Wincy Spider, Little Bo-Peep, and many more! These classic rhymes we all know and love so well are perfect for bedtime reading and will allow parents and young ones to enjoy them time and time again. Children aged 0-5 will love pouring over the colorful illustrations that accompany and enrich the rhymes by bringing the quirky characters to life.